Mechanistic Analysis of the Broad Antiretroviral Resistance Conferred by HIV-1 Envelope Glycoprotein Mutations - Yuta Hikichi (American Society for Microbiology, 2021)
Although combination antiretroviral (ARV) therapy is highly effective in controlling the progression of HIV disease, drug resistance can be a major obstacle. Recent findings suggest that resistance can develop without ARV target gene mutations.